Women's empowerment and its link to intimate partner violence and contraceptive use in selected Southeast Asian countries / Ang Chiew Way - Ang , Chiew Way (2022)
Achieving gender equality is essential for the sustainable development of developing countries. Since 1994, the United Nations Population Fund has declared that reproductive rights are fundamental human rights, and uplifting women’s status is a crucial component in improving their well–being. Many efforts to empower women have been made by global leaders following the adoption of the Millennium Development Goals and the Sustainable Development Goals. However, to date, gender inequality remains one of the most prevalent global challenges. In addition, gender inequality exposes women to intimate partner violence (IPV). It further limits women’s access to modern contraception. Many past studies have found that women’s empowerment is one of the main determinants influencing sexual and reproductive health and rights. Hence, this study aims to 1) identify the measures of women’s empowerment at the household level; 2) examine the level of women’s empowerment and its determinants, and 3) examine the association between women’s empowerment and sexual and reproductive health and rights, specifically IPV and modern contraceptive use in selected Southeast Asian countries. This study focuses on Cambodia, Indonesia, Myanmar, and the Philippines because these countries represent the three major religions, Buddhism, Christianity, and Islam, practiced in Southeast Asia. In addition, the concept of male dominance in Asian society often places women in an inferior position whereby their authority in leadership and decision–making is suppressed. As such, women are often neglected, thus being less empowered in society. This study utilizes the latest data obtained from the Demographic and Health Survey conducted in Cambodia, Indonesia, Myanmar, and the Philippines. The sample for this study includes all women of the reproductive age (15 to 49 years) who are currently married or in a union. Exploratory factor analysis is applied to determine the measures of women’s empowerment. Logistic regression is used to identify the factors influencing women’s empowerment and its association with IPV and modern contraceptive use. The measures of women’s empowerment include women’s household decision–making power, women’s asset ownership, and women’s attitude towards wife–beating. The results show that demographic and socioeconomic factors strongly influence women’s empowerment. Education, work status, and exposure to mass media are significantly associated with women’s empowerment across the countries. In turn, women’s empowerment influences IPV and modern contraceptive use but its effect varies across the countries. Women’s empowerment affects IPV and modern contraceptive use in Cambodia and the Philippines. In Indonesia, women’s empowerment is significantly associated with modern contraceptive use. For Myanmar, the associations of women’s empowerment with IPV and modern contraceptive use are insignificant in the multivariate context. In addition, women with greater exposure to mass media have a lower prevalence of experiencing sexual IPV in the Philippines, while those who have received secondary school education and are working in Cambodia have lower odds of experiencing IPV. The findings of this study provide inputs for policymakers in designing specific policies to improve the status of women.